EFEKTIFITAS PENGGUNAAN BUAH KURMA TERHADAP PENINGKATAN HEMOGLOBIN PADA REMAJA PUTRI DI SMAN 1 TOLANGOHULA - Sriyulita Puspita Abdjul; Harismayanti Harismayanti; Abdul Wahab Pakaya (Pusat Riset dan Inovasi Nasional, 2023)
The prevalence of anemia in Indonesia according to the RI Ministry of Health in 2018 namely21.7% with anemia sufferers aged 5-14 years by 26.4% and 18.4% sufferers aged 15-24 years. Anemia is not handled properly can have an impact on adolescents, including lowering the body's resistance thereforeit is susceptible to disease, decreased activity and learning achievement due to reduced concentration. This can be handled by consuming dates, because dates have a higher iron content, the iron content in dates can increase hemoglobin levels. The objective of research was to analyze the differences in hemoglobin levels before and after the use of dates in young women at SMAN 1 Tolangohula. The research design was quasi-experimental with a pre-post control group design. The sample was 30 respondents using a purposive sampling technique. The instruments used are Quick Check and Observation sheets. Using a statistical test paired t-test, with a significant level of α (0.05). The results were obtained in the treatment group before being given dates, there were 12 girls (80%) with normal HB and 3 people (20%) with abnormal HB. While the results in the control group of 15 girls were 14 (93.3%) girls with abnormal HB levels and 1 (6.7%) girls with normal HB levels. With a pvalue of 0.000. it can be concluded giving dates is effective in increasing hemoglobin in female adolescents at SMAN 1 Tolangohula.